PERSEPSI GURU TENTANG PELAKSANAAN SUPERVISI PEMBELAJARAN OLEH KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA NEGERI KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Fetrianis (Universitas Negeri Padang, 2013)
This research is based on the problem that shown the principals learning supervisionwhich were not very good. This research has a purpose to get the information about teacher’s perception toward the principals learning supervision at SMP Negeri Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota. The type of this research is descriptive. The population of this research is 106 people. The sample which taken is 43% of the population, 46 people. The data collsed is likert scale quisionare model. This quisionare has been tested the validity and the reliability. The data is analyzed by average formula. In general, the teacher’s perception toward principals learning supervision at SMP Negeri Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota on the enough good category with average score 3,4. Keyword: Principals Learning Supervision